The Challenges of Sharia Fintech Regulation in Indonesia: A Global Comparative Analysis - Darmadi Durianto; Dahniarti Hasana; Nur Fareha; Dewi Nadya Maharani (Unissula, 2025)
The purpose of this study is to analyze Sharia-compliant fintech regulations in both countries and provide recommendations to strengthen their regulatory frameworks. Financial technology (fintech) has transformed the global financial industry landscape by introducing innovations that accelerate access to financial services. Sharia-compliant fintech, as part of this development, plays a critical role in providing financial services that comply with Sharia principles, such as the prohibition of riba, gharar, and maysir. The study found that Sharia-compliant fintech regulations in several countries, such as Indonesia and Bangladesh, are still in their infancy. Existing regulations are often not fully aligned with the needs of Sharia-compliant fintech, highlighting the need for a more comprehensive and inclusive regulatory approach. In Indonesia, the Financial Services Authority and Bank Indonesia have issued several policies to support fintech development, but there is still no specific regulation for Sharia-compliant fintech. In Bangladesh, the development of Sharia-compliant fintech is supported by Islamic banking initiatives, although a more mature regulatory framework is still needed. By adopting best practices from countries such as Malaysia, which have developed more advanced regulations for Sharia-compliant fintech, both countries can increase financial inclusion and create a more sustainable fintech ecosystem.